Cebocephaly in an infant with trisomy 18. Issue 4 (August 1977) - Hunter, A G; Ray, M; Langston, C
Abstract : An infant who died in the perinatal period with the unusual association of trisomy 18 and cebocephaly is described. It is suggested that this association may be more common than is generally recognised because the majority of such infants are stillborn or live only briefly and often do not have chromosome studies performed.